Use of neelalohit in the management of duchenne muscular dystrophy in Nepal. - Giri,Shri Krishna; Rupakheti,Dinesh (2020)
Executive Summary; Duchenne Muscular Dystrophy (DMD) is a progressive disorder affecting striated and cardiac muscles.DMD is a severe, progressive disease that affects 1 in 3600-6000 live male births. Some 25,000 males in Nepal are suffering from various types of muscular dystrophy (MD) disorder, a human genetic disorder that is not curable. This study intends to evaluate the effectiveness of "Neelalohit" therapy in the management of DMD that is based on oriental system of healing. If the therapy is proven to be effective, it can prevent many deaths, reduce financial burden to the country and improve quality of life of people. An interventional study pre post design without control was carried out in among five purposively selected participants who were clinically diagnosed having DMD. The study was conducted on National Ayurvedic Research and Training Centre, Kirtipur, Kathmandu, Nepal from September 17-October 31, 2017 (Asoj 1-Kartik 14, 2074) for 45 days in hospital and the follow up period for 2 months then after. The study participants were hospitalized for first 45 days and provided oral powder, applicant/ paste, spray and massage oil. On completion of 45 days, participants was discharged from hospital and called for follow up with continuation of medicine (oral powder) for 225 days with clear instructions on the doses of medicines. But, the study could only be continued for 2 months due to interruption of supply of medicine. The pre-intervention assessment was taken and the intervention was provided to the participants. The assessment was done first in a week and then in 20 days duration i.e. in 27th days and 46th days. The assessment includes MRC grading, range of motion, Gower's sign and muscle girth. Laboratory investigation was done before intervention, in 21st days and after 45 days of intervention. The data were collected through systematically designed proforma. The data analysis was done in IBM-SPSS ver21. A participant belongs to 7 years whereas rest two belongs to 9 years and two belongs to 12 years. Comparing the change in MRC grading between pre intervention and two months follow up after 45 days of hospitalization, there was increase in the median score of MRC grading on shoulder, left arm pronator and supinator of both arms, wrists, hand, hip, ankle and foot whereas the MRC grading of knee and pronator of right arm remains the same. The change in range of motion was also remarkable. The CPK value of has also been decreased in two participants. The six minute walking distance has been increased in a patient while it has been decreased in the other (3 out of 5 are immobile). The increase in range of motion is also seems remarkable. The MRC grading also showed the remarkable progress after the intervention. The Neelalohit system of treatment for Duchenne Muscular Dystrophy was found effective in increasing the muscle power and range of motion of the DMD patient in the 45 days intensive trial and 2 months follow up. The CPK value of two patients was also decreased. The physical activities of the patients has not been deteriorated. Also, no harmful effects were observed during study clinically as well as in laboratory test. The study was conducted in a small sample size (only five). The study should include adequate sample size and of longer duration.